2010
DOI: 10.1159/000312881
|View full text |Cite
|
Sign up to set email alerts
|

Is Anemia at Hospital Admission Associated with In-Hospital Acute Kidney Injury Occurrence?

Abstract: Background: The effect of acute kidney injury (AKI) on anemia has been well-documented. However, the effect of ‘preexisting’ anemia on AKI has been less addressed. The aims of the present study were to investigate (1) the association between anemia at hospital admission and AKI occurrence, and (2) the effect of ‘preexisting’ anemia on the clinical outcomes of AKI. Methods: A retrospective cohort study was undertaken among patients aged ≧17 years who were admitted to our hospital during the year 2006 (n = 34,80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
0
13
0
3
Order By: Relevance
“…Although the mechanism of the RDW values in patients with AKI is at present unclear, several potential explanations may account for the relationship between RDW and AKI. Among the risk factors, anemia is the independent related to AKI [46], one present study indicated that the elevated RDW group in AKI was found to have low red blood cell (RBC) which may contribute to increase AKI occurring [28]. Previous studies have demonstrated RDW levels are associated with inflammation and serum antioxidants which mediate effects on RDW through IL-6 [47], and the IL-6 levels in serum may predict the mortality of AKI patients [48].…”
Section: Discussionmentioning
confidence: 60%
“…Although the mechanism of the RDW values in patients with AKI is at present unclear, several potential explanations may account for the relationship between RDW and AKI. Among the risk factors, anemia is the independent related to AKI [46], one present study indicated that the elevated RDW group in AKI was found to have low red blood cell (RBC) which may contribute to increase AKI occurring [28]. Previous studies have demonstrated RDW levels are associated with inflammation and serum antioxidants which mediate effects on RDW through IL-6 [47], and the IL-6 levels in serum may predict the mortality of AKI patients [48].…”
Section: Discussionmentioning
confidence: 60%
“…In this study, patients with an RDW greater than 14.1% showed lower RBC indices than did those with an RDW less than 14.1%. Because anemia is a risk factor for AKI [ 35 ], the low RBC indices found in the elevated RDW group might contribute to increase the odds of stage 3 AKI occurring.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple settings, POA anemia has been associated with increased risk for acute kidney injury, 3 worse outcomes in the setting of stroke, 4 and acute coronary syndromes. 14,15 However, most studies do not report the relative contribution of POA anemia and HAA to patient outcomes.…”
Section: Principal Findingsmentioning
confidence: 99%